Ang makinis na pagsulat sa pamamagitan ng paggamit ng mabisang pananalita - Reyes, Rosalina T. 1926- (s.n.], 1971)
This paper gives a linguistic description of five different techniques for teaching refinement in writing, and presented some instructional materials. The techniques includes exactness in the choice of synonyms, specificity in word-choice with respect to the five senses, compounding of words, use of connotations and use of figures of speech. Each technique is accompanied by explanation, some exercises and a lesson plan.